A domestic dilemma: The effect of Foreign Account Tax Compliance Act (FATCA) on our bank secrecy law - Segundo, Karissa Inez A. (Animo Repository, 2015)
This thesis places focus on the effect of Foreign Account Tax Compliance Act (FATCA) on Philippine banking and its repercussions as regards the strict laws on account disclosures and exchange of information. FATCA, as a U.S law, is outside the scope of Philippine jurisdiction. However, such law covers all “U.S persons” or those with “U.S indicia”. As a consequence, domestic banks may be compelled to comply whenever American clients are involved as such law imposes a 30% withholding tax penalty on U.S income for non-compliance. This work starts by discussing the Philippine bank secrecy laws which provide for absolute confidentiality of account deposits as well as discussing the reason behind FATCA in combating offshore tax fraud and evasion. The proponent also discusses laws in different jurisdictions having the strictest bank secrecy such as Switzerland, Lebanon, Singapore, and Luxembourg. The proponent also ascertains the effect of FATCA on these countries considering the strict nature of account deposits in these jurisdictions. Through this, the proponent can compare the bank secrecy laws of these countries to that of the Philippines, as well as get information on how these countries dealt with FATCA and apply it in the current situation of the domestic banks having to be put at risk of violating bank secrecy laws by complying with FACTA. This study shows how great FATCA impacts the bank secrecy laws and will give the readers a broad range of information in regard the status of confidentiality of account deposits worldwide. This thesis recognizes the right of depositors to be protected under the Philippine law. The proponent maintains that account deposits or other deposit information must be kept confidential, subject to exceptions provided by law and the principles of international law, because sovereignty dictates that a foreign law cannot override domestic legislation.